Development of Coffee Product Downstream Through The Omah Kopi Community in Tirtoyudo Malang - Azis, Abdul; Arifa, Laily Nur (Abdi: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
The coffee industry in Indonesia has experienced significant growth in recent years, with Tirtoyudo Village in Malang Regency becoming a key production center, yielding up to 1,949 tons annually. Despite its potential and cultural heritage, coffee farmers in Tirtoyudo face economic challenges due to low market prices set by 'cino dampit.' This community service project aimed to empower the local community and optimize the region's coffee potential through the Asset-Based Community Development (ABCD) approach, focusing on value-added product development and innovative marketing strategies. The activities included analyzing the local coffee potential, providing training on derivative product creation—such as coffee perfume and aromatherapy candles—and conducting workshops on branding, packaging, and digital marketing. By applying the ABCD approach, the project enabled the community to recognize and leverage their resources to create high-quality products under the "Kopi Tirtoyudo" brand. Results showed increased community capacity in coffee processing, branding, and marketing, enhancing product marketability and economic resilience. The initiative also strengthened the village's cultural identity and positioned Tirtoyudo as a competitive player in the national coffee industry. This holistic approach highlights the importance of collaboration between communities, educational institutions, and support entities in achieving sustainable rural development. The outcomes suggest that similar strategies can be replicated in other regions to empower local economies. Continued support in technology access, marketing, and distribution is essential for ensuring the sustainability of such initiatives. Tirtoyudo Village is a model for integrating traditional knowledge with modern practices to promote economic growth and community welfare.